Enthalpy of formation and disordering temperature of transient monotropic liquid crystals of poly(butylene 2, 6-naphthalate). (5th December 2018) - Androsch, René; Soccio, Michelina; Lotti, Nadia; Jehnichen, Dieter; Göbel, Michael; Schick, Christoph
Abstract: Melt-crystallization of poly(butylene 2, 6-naphthalate) (PBN) at temperatures lower than about 160 °C follows Ostwald's rule of stages via intermediate formation of a smectic liquid crystalline phase (LC-phase). The transient LC-phase has been isolated by interruption of the isothermal crystallization process at 140 °C at sub-second timescale, and then its disordering was analyzed on heating at a rate of 2000 K/s, which suppresses the transition into α-crystals. The disordering temperature of the LC-mesophase is slightly lower than 200 °C, and as such 20–30 K lower than the melting temperature of α-crystals formed from the LC-phase at 140 °C. Analysis of the bulk enthalpy of formation of the LC-phase revealed that it covers only 20–25% of the total bulk enthalpy of crystallization, which is considered further proof of its smectic nature. Graphical abstract: Highlights: Crystallization of PBN below 160 °C follows Ostwald's rule of stages. Crystallization below 160 °C proceeds via formation of a liquid crystalline (LC) phase. Disordering of the LC-phase was analyzed on fast heating, suppressing the transition into crystals. Disordering of the LC-phase occurs 20–30 K lower than melting of α -crystals. The bulk enthalpy of LC-phase formation is about 20–25 % of that of crystallization.